2015
DOI: 10.1021/acsnano.5b03592
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Adsorption Affinities of Small Molecules on Carbon Nanotubes Using Molecular Dynamics Simulation

Abstract: Computational techniques have the potential to accelerate the design and optimization of nanomaterials for applications such as drug delivery and contaminant removal; however, the success of such techniques requires reliable models of nanomaterial surfaces as well as accurate descriptions of their interactions with relevant solutes. In the present work, we evaluate the ability of selected models of naked and hydroxylated carbon nanotubes to predict adsorption equilibrium constants for about 30 small aromatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
151
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(157 citation statements)
references
References 118 publications
5
151
1
Order By: Relevance
“…Comer et al calculated the binding energy profile of the binding of a few organic molecules, that were used in BSAI studies (described in the next section), onto graphenic surfaces. Subsequently, equilibrium binding coefficients were calculated and compared to experimental results (Figure (b)) . Such comparisons provide solid grounds for the deduction of exact chemical composition and spatial arrangements of the surface ligands.…”
Section: Modeling Of Nanomaterials Interactions—physical Statisticalmentioning
confidence: 99%
See 1 more Smart Citation
“…Comer et al calculated the binding energy profile of the binding of a few organic molecules, that were used in BSAI studies (described in the next section), onto graphenic surfaces. Subsequently, equilibrium binding coefficients were calculated and compared to experimental results (Figure (b)) . Such comparisons provide solid grounds for the deduction of exact chemical composition and spatial arrangements of the surface ligands.…”
Section: Modeling Of Nanomaterials Interactions—physical Statisticalmentioning
confidence: 99%
“…(d) Comparison of the logarithm of the adsorption equilibrium constant measured in experiment and the same quantity calculated in simulation for all 29 adsorbates. The full names of the chemicals can be found in the referenced publication . (Reprinted with permission from Ref .…”
Section: Modeling Of Nanomaterials Interactions—physical Statisticalmentioning
confidence: 99%
“…Alternatively,c lassical molecular dynamics simulations with atomistic models and explicit solvent have arisen as ap romising approach to elucidating interactionsb etween commonn anomaterials and organic molecules. [42] In this work, we report on an in-depth investigation of the supramoleculara ssembly of small-molecule derivativesw ith insoluble carbon-based nanotubes governed by noncovalent interactions through ac ombined experimental andc omputational quantitative approach. [40] Likewise, Ulissi et al [41] have reported the free energies of adsorption of more than 50 compoundso nag raphenic surface; these show ag ood correlation with the predictions of structure-activity models.…”
Section: Introductionmentioning
confidence: 99%
“…Given its hydrophobicity and sp 2 carbon atom structure, graphene can interact with aromatic organic chemicals through hydrophobic and π–π interactions. Owing to its excellent interaction properties, graphene offers several opportunities and innovative solutions in various applications, such as contaminant removal and drug delivery 57 . However, graphene nanomaterials could be released into aquatic environments during the manufacture, use, and disposal of graphene-enabled products 8, 9 .…”
Section: Introductionmentioning
confidence: 99%